ANALISIS PERUBAHAN KEBIJAKAN DAN DAMPAKNYA TERHADAP TARIF PPN 11% - Sitanggang, Klose Margaret Oktavia; Kiranan, Nanda Wahyu Indah (Jurnal Riset Akuntansi & Keuangan, 2025)
The study aims to analyze the policy taken by the government regarding the change in value-added tax rate of 11% and the impact of the policy on society and companies. The qualitative method used to collect data is a literature study, with data sources obtained from secondary sources. The application used is “Publish or Perish” which aims to access relevant journals from Google Scholar with search settings covering the period 2022-2024, with a maximum limit of 100 journals searched. The keywords used in the search were “Value Added Tax”, “COGS Law”, and “11% VAT Rate”. The results found that one of the policies carried out by the government in order to increase state revenue was to increase the value added tax rate to 11%. The policy was carried out because in previous years the government budget had experienced greater expenditure than income or what is commonly called a budget deficit. In addition, the Covid-19 that occurred in Indonesia also worsened state revenues. With the increase in the value-added tax rate, it is able to increase state revenue. However, the increase made the price of basic goods soar, causing inflation to occur.